IMPLEMENTATION OF THE PROJECT BASED LEARNING MODEL TO SUPPORT STUDENTS' COLLABORATION SKILLS AND LEARNING MOTIVATION - Fauzan, Rizki (Universitas Jember, 2025)
This research is motivated by the decline in the quality of learning on the mutual cooperation indicator based on the results of the educational report in 2025 and the low interest of students in Physics subjects at SMA Negeri 1 Moga. The study aims to describe and analyze the extent to which the implementation of the Project Based Learning (PjBL) model supports collaboration skills and learning motivation of class XII A-C students. The research method is descriptive-quantitative with a sample of 108 students. Data were collected through a Likert scale questionnaire that has been tested for validity and reliability and analyzed using descriptive statistics. The results showed an average score of collaboration skills of 105.21 in the good category with the strongest indicator in interdependence with an average of 21.96 and the weakest in group processing with an average of 19.72. Learning motivation reached an average of 73.1 in the fairly good category, most strongly influenced by choice or interest in tasks with an average of 28.00 and weakest by the aspect of perseverance or tenacity with an average of 11.70. The implementation of PjBL has the potential to improve students' collaboration skills and learning motivation, but it is necessary to strengthen learning strategies to improve group processing and persistence in completing projects.